2020
DOI: 10.1038/s41598-020-76397-4
|View full text |Cite
|
Sign up to set email alerts
|

Melanin concentration and depolarization metrics measurement by polarization-sensitive optical coherence tomography

Abstract: Imaging of melanin in the eye is important as the melanin is structurally associated with some ocular diseases, such as age-related macular degeneration. Although optical coherence tomography (OCT) cannot distinguish tissues containing the melanin from other tissues intrinsically, polarization-sensitive OCT (PS-OCT) can detect the melanin through spatial depolarization of the backscattered light from the melanin granules. Entropy is one of the depolarization metrics that can be used to detect malanin granules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Another important limitation is the polarization state of incident light. DOPU measurements are known to highly dependent on the incident light polarization state 34 36 . Previous studies of DOPU, mainly performed at the Medical University of Vienna 14 , 18 , 31 , used a circularly polarized incident beam.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation is the polarization state of incident light. DOPU measurements are known to highly dependent on the incident light polarization state 34 36 . Previous studies of DOPU, mainly performed at the Medical University of Vienna 14 , 18 , 31 , used a circularly polarized incident beam.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation is the state of polarization of incident light. DOPU measurement is known to highly depend on the incident polarization state 38 40 . Our PS-OCT system used single-mode optical fibers in the sample arm 16 , and the polarization state of the incident beam to the eye was not fully stable and may have varied among measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed principles of our PS-OCT technology and the associated formula used in this study have previously been reported [ 27 , 28 ]. In brief, the light source used in an optical interferometer of the PS-OCT was a frequency-swept laser (Axsun Technologies, Billerica, MA, USA); its central wavelength, sweep repetition frequency, and wavelength range were 1.05 μm, 100 kHz, and 100 nm respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As one of the approaches to overcome the limitation in DOPU, Yamanari et al introduced a mathematical framework to compute “entropy” that represents the randomness of the polarization property in an advantageous way, both physically and mathematically [ 27 ]. We have previously reported that Entropy in PS-OCT is a parameter that is independent of the incident polarization state and that in principle it is highly reproducible in retake [ 28 ]. Furthermore, high reproducibility of entropy values in normal eyes also has been reported [ 29 ].…”
Section: Introductionmentioning
confidence: 99%